RURAL POOR AND RURAL HEALTH CARE IN NIGERIA: A CONSOCIAL NEED FOR POLICY SHIFT - Sunny Nwachukwu Nnabuihe; Etemike Lizzy; Nwachukwu Tobechukwu Odunze (European Scientific Journal, ESJ, 2015)
Rural poor have lived in the shadow of overriding concern for the prosperity, development and needs of urban or state government. Much attention on the urban areas has been on the growth of capital, financial interests and social infrastructural amenities which of course has debar and ignore rural interest. The negative impact has affected the rural people. There is need to rethink the goals and process of rural development to ensure more positive outcomes for communities, people and the overall environment. The focus of this paper is on the participation of social service organization on the development of rural and remote areas in Nigeria. This paper provides a framework from which a revised model rural development is derived. These models on rural development emphasize the full participation of government in the process of rural changes.